Хүүхдийн аялгуут аман зохиолын төрөл зүйлс ардын урлагийн үндэс болох нь: Children`s songs as foundation of folk art - Л., Хэрлэн (Mongolian Studies, 2023)
Genres of Mongolian folklore and oral melody were not only foundations for singers and storytellers; they were also teaching methods and clever ways to train children. Genres of children’s folklore are basics of folk art. The origin and development of magnificent Mongolian long songs are a near perfect glimpse of the teaching methods and rituals of Mongolians.